Implementasi nilai pancasila sila ketuhanan yang maha esa masa pembelajaran daring pada peserta didik sekolah dasar - Jaka Sarwanto; Hasan Mahfud; Roy Ardiansyah (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
The precepts of the One and Only Godhead are the first precepts of Pancasila,which animate the other four precepts. The precepts of the the One and Only Godhead have a relationship between humans and the Creator, which then the other four precepts are guidelines for the relationship between humans with one another. This research is a qualitative research using the case study method. 11 students of class fifth Purwotomo State Elementary School No.97 Surakarta were selected as subjects in this study. Analysis of the data in the study used the interactive analysis technique of the Miles and Huberman model. The results of this study indicate that the value of the precepts of the One and Only Godhead has been implemented by students even though in the online learning period with an indication that the three indicators have been carried out, but in its implementation for the first indicator it is still not optimal because the implementation of worship is still not on time and memorization ofprayers. daily students are still small. This is mostly due to the factors of habituation, guidance and supervision from each parent.